Gestión de estrategias ambientales y desarrollo de la competencia indaga mediante el método científico área ciencia y tecnología, Chepén 2018 - Díaz Rodas, Doris Claritza (2022)
The objective of this research work is to determine the degree of effectiveness of the management of the environmentalstrategies program in the competence investigates through the scientific method to build knowledge, of the fourth grade students of the "Carlos Gutiérrez Noriega" Educational Institution, Chepén, 2018. For the preparation of this report, the study sample is made up of 21 students, whose ages fluctuate between 09 and 11 years and who are in the fourth grade of the Primary level of the Educational Institution "Carlos Gutiérrez Noriega", Chepén - 2018, the type of The study is experimental with a pre experimental design with pre and posttest, a questionnaire was applied to the sample that measured the dependent variable, said instrument went through the validation and reliability processes, in this way the seriousness of the tests can be ensured. results that we publish and thus be able to be a source of consultation for future research. After data collection and analysis, the research hypothesis was verified with 95% confidence levels, resulting in the main conclusion that: The management of the environmental strategies program is highly effective over the competence investigatesthrough the scientific method to build knowledge, in the fourth grade students of Primary Education of the Educational Institution 'Carlos Gutiérrez Noriega', Chepén, 2018, justified in the comparison of average scores where the average of the post-test (16.48 points), higher, compared to the average was reflected of the pre-test (8.24 points), analyzed by the Student's T-Test, when obtaining a probability of significance p = 0.000 less than the significance level 0.05; and with a confidence level of 95%.